2011
DOI: 10.1111/j.1365-2036.2011.04667.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the effects of antitumour necrosis factor-α on bone metabolism in inflammatory bowel disease

Abstract: SUMMARY BackgroundPatients with inflammatory bowel disease (IBD) are at increased risk of osteoporosis. A number of studies have emerged in recent years indicating that tumour necrosis factor (TNF) blockade appears to have a beneficial effect on bone mineral density (BMD) in IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 73 publications
2
29
1
1
Order By: Relevance
“…Previously it gained much attention for its role of inducing apoptosis of cells via activation of NF-κB and caspase pathways (MacFarlane, 2003). However, TNF-α could elicit complicated biological effects through binding to its receptors followed by activation of numerous intracellular signals ( Caminero et al, 2011, Rosenblum and Amital, 2011, Veerappan et al, 2011and Vujanovic, 2011. Since ETB2 receptors are not expressed in VSMC under normal conditions, but was impressively induced by short-term exposure to TNF-α during organ culture, which is also observed in patients with CVD, we were interested in the underlying mechanisms that may extend our knowledge of the toxic effects of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Previously it gained much attention for its role of inducing apoptosis of cells via activation of NF-κB and caspase pathways (MacFarlane, 2003). However, TNF-α could elicit complicated biological effects through binding to its receptors followed by activation of numerous intracellular signals ( Caminero et al, 2011, Rosenblum and Amital, 2011, Veerappan et al, 2011and Vujanovic, 2011. Since ETB2 receptors are not expressed in VSMC under normal conditions, but was impressively induced by short-term exposure to TNF-α during organ culture, which is also observed in patients with CVD, we were interested in the underlying mechanisms that may extend our knowledge of the toxic effects of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Az ALP izoformái szerkezetben, kinetikus tulajdonságokban, molekulaméretben és izoelektromos pontban különböznek [2]. A rutinvizsgálatok során diagnosztizált hyperphosphatasaemiának számos oka lehet, amelyek dön-tően máj-vagy csonteredetűek.…”
Section: áBraunclassified
“…DeBoer et al [126] have shown, using a dextran sodium sulfate induced colitis model, that mice treated with anti-TNF-α antibodies demonstrated a partial normalization of pubertal timing coincident with decreased systemic inflammation. Bone metabolism is also positively affected by infliximab, at least in the short-term, manifested by improved bone formation markers [127,128].…”
Section: Biologic Treatmentmentioning
confidence: 99%